Using the Abbreviated Version of Modification of Diet in Renal Disease Formula as A Primary Estimate for the Prevalence of Undiagnosed Chronic Kidney Disease in Patients with Acute Stroke - Al Saedi, Ali J.; Al Shameri, Mohammed , H.; abdul Jabbar, Mohammad; Kareem, Abdul Hakeem A.; Mal Allah, Zuhair; Ferooz, Mutaaz; Al Shameriͨ, Basim (AL-Kindy College Medical Journal, 2013)
Introduction: The association between acute stroke andrenal function is well known. The aim of this study is toknow which group of patients with acute stroke is morelikely to have undiagnosed Chronic Kidney Disease andwhich risk factors are more likely to be associated with.Methods:We studied 77 patients who were diagnosed tohave an acute stroke.Patients were selected betweenApril2011andJune 2011 using the " 4-variableModification ofDiet in Renal Disease Formula " which estimatesGlomerular Filtration Rate using four variables :serumcreatinine ,age ,race and gender.Results :The study included 38 male and 39 femalespatients ,aged (35-95) years. Glomerular Filtration Rate inpatients with acute stroke was calculated and showed37.6% , 28.5% , 25.6% , 6.4% and 2.5% (Chronic KidneyDisease stage 0, 1,2,3,4,5 respectively.)Conclusion :One Third of patients with acute stroke hadGlomerular Filtration Rate less than 60ml/min per 1.73m²patients who had more than 2 risk factors of ChronicKidney Disease are about 3 times more likely to haveGlomerular Filtration Rate less than 60 ml/min per1.73m² to those with 2 or less risk factors